An advanced approach for distortionless seamcarving in video analysis - Thirumalaiah, G.; Immanuel Alex Pandian, S. (International Journal of Engineering and Technology, 2019)
Video synopsis is a technique that creates summary of the video or it can converts the abstraction of selected frames. This innovative approach permits the organizations to review long videos in minutes. It is more convenient to superimpose objects on to the static background and parallel displaying events to generate video synopsis. In this, paper a propelled noiseless video synopsis technique, which utilizes object-extracting method for vital objects. Along this technique spatial and temporal coherence cost is used to maintain time and position of the important objects. The proposed method will generate video spots and seam craving method to reduce the input (original) video. Finally, experimental results gives that our proposed method can produce a large reducing ratio, while preserving all the important objects of choice. Therefore, this noiseless approach can facilitate users to watch the surveillance video with greater accuracy.Â Â